The lexicons as symptoms of the existence of individuals in the universe of the web - Castañeda Bustamante, Heiner (Estudios de Filosofía, 2011)
This article poses a reflection on the multiple lexicons that are constructed in the Internet stage as opposed to the Great Philosophical Lexicon that faces the direct participation of individuals which, once turned into discourse, come to life in the stage of the Web, and embrace diverse conceptions of the world under the protection of the Pragmatisn applied to the environment of Virtual Reality, where the assessment of concepts associated with Simulation, Identity, Certainty or Falsity, acquires different hues and forces a combined dialogue that makes Dogmatisms totter in favor of a collective construction of the universes of those who navigate on the Web and leave there their discursive mark as a symptom of existence.